Reporting of Corporate Social Responsibility by Using the Program Communication - Nikolov, Emil (Research Papers, 2018)
This article researches the Corporate Social Responsibility reporting by Bulgarian enterprises through the use of the most widespread global “framework” for releasing non-financial information – Communication on Progress of the UN Global Compact. We have analyzed the quantitative and qualitative characteristics of communications published by Bulgarian enterprises; in addition, we have identified the existing problematic areas. The research results demonstrate that Bulgarian enterprises do not make full use of the possibilities of the communications as a tool for reporting Corporate Social Responsibility.
Keywords: Communication on progress; United nation global compact; Corporate social responsibility reporting